The Interaction of CD97/ADGRE5 With β-Catenin in Adherens Junctions Is Lost During Colorectal Carcinogenesis - Hilbig, Doris; Dietrich, Norman; Wandel, Elke; Gonsior, Susann; Sittig, Doreen; Hamann, Jörg; Aust, Gabriela (Frontiers in Oncology, 2018)
The adhesion G protein-coupled receptor CD97/ADGRE5 is present in adherens junctions of human normal intestinal cells and upregulated in colorectal carcinomas. Here, we examined whether CD97 directly interacts with junctional proteins in human normal and malignant colorectal tissue. We identified an association of CD97 with β-catenin using a proximity ligation assay and confirmed the interaction between both endogenous proteins at the biochemical level by co-immunoprecipitation in human and mouse tissues and cell lines. GST-pulldown revealed that CD97 binds β-catenin through its seven-span transmembrane/intracellular domain(s). To study tumour-associated changes in the interaction of CD97 and β-catenin in situ, we quantified and correlated both proteins at the membrane, and in the cytoplasm and nuclei of human colorectal carcinomas and their corresponding normal tissues (n=111). In normal colon, membranous levels of CD97 and β-catenin correlated strongly (p<0.0001). To some degree both molecules disappeared in carcinomas simultaneously from the membrane of tumour cells (p=0.017). CD97 accumulated in the cytoplasm, whereas β-catenin emerged in the cytoplasm and nuclei. CD97 and β-catenin levels in the cytoplasm correlated well (p<0.0001). Irrespective of their subcellular localization, interaction of CD97 with β-catenin in tumour cells was restricted to the cell contacts. Accordingly, CD97 did not regulate β-catenin-dependent TCF-mediated transcriptional activity. In summary, while CD97 and β-catenin interact in adherens junctions, their interaction is lost and both molecules follow different functional paths inside tumour cells.